The anthropology of Catholicism : a reader - Norget, Kristin; Napolitano, Valentina; Mayblin, Maya (University of California Press, 2017)
"Aimed at a wide audience of readers, The Anthropology of Catholicism is the first companion guide to this burgeoning field within the anthropology of Christianity. Bringing to light Catholicism's long but comparatively ignored presence within the discipline of anthropology, the book introduces readers to key studies in the field, as well as to current analyses on the present and possible futures of Catholicism globally. This reader provides both ethnographic material and theoretical reflections on Catholicism around the world, demonstrating how a revised anthropology of Catholicism can generate new insights and analytical frameworks that will impact anthropology as well as other disciplines"--Provided by publisher